WDR2 regulates the orphan kinesin KIN-G to promote hook complex and Golgi biogenesis in Trypanosoma brucei - Qing Zhou; Huiqing Hu; Ziyin Li (mBio)
ABSTRACT The flagellum in Trypanosoma brucei plays crucial roles in cell locomotion, cell morphogenesis, and cell division, and its inheritance depends on the faithful duplication of multiple flagellum-associated structures. One of such cytoskeletal structures is a hairpin-like structure termed the hook complex, composed of a fishhook-like structure and a centrin arm structure, whose cellular functions remain poorly understood. We recently identified KIN-G, an orphan kinesin that promotes hook complex and Golgi biogenesis. Here we report a WD40 repeat-containing protein named WD40 Repeat-containing protein 2 (WDR2), which interacts with and regulates KIN-G. WDR2 co-localizes with KIN-G at the centrin arm, and knockdown of WDR2 disrupts hook complex integrity and morphology, inhibits flagellum attachment zone elongation and flagellum positioning, and arrests cytokinesis. Knockdown of WDR2 also disrupts the maturation of the centrin arm-associated Golgi apparatus, thereby impairing Golgi biogenesis. WDR2 interacts with KIN-G via the N-terminal domain of unknown function, the middle domain containing a coiled-coil motif and a PB1 motif, and the C-terminal WD40 domain, and targets KIN-G to its subcellular location. These results uncover a regulatory role for WDR2 in recruiting KIN-G to regulate hook complex and Golgi biogenesis, thereby impacting flagellum inheritance and cell division plane positioning for a symmetrical cytokinesis.IMPORTANCETrypanosoma brucei is a unicellular eukaryotic parasite and the causative agent for sleeping sickness in humans and nagana in cattle in sub-Saharan Africa. This parasite has a motile flagellum, which controls cell morphogenesis and cell division. The flagellum associates, at its proximal region, with a specialized cytoskeletal structure termed the hook complex, which comprises a fishhook-like structure and a bar-shaped structure named the centrin arm. The Golgi apparatus associates with the centrin arm and depends on the latter for biogenesis. We previously discovered an orphan kinesin named KIN-G that plays essential roles in promoting hook complex and Golgi biogenesis. Here we identified a KIN-G-interacting protein named WDR2, which regulates KIN-G localization and stability and promotes hook complex and Golgi biogenesis. These results discovered a new protein complex at the centrin arm and uncovered a mechanistic role of WDR2 in recruiting KIN-G to regulate the biogenesis of the hook complex and the Golgi apparatus, further impacting flagellum inheritance and cell division in this early divergent protozoan parasite.